The potassium channel K2P2.1 shapes the morphology and function of brain endothelial cells via actin network remodeling - Stefanie Lichtenberg; Laura Vinnenberg; Falk Steffen; Isabelle Plegge; Nicholas Hanuscheck; Vera Dobelmann; Joel Gruchot; Christina B. Schroeter; Haribaskar Ramachandran; Beatrice Wasser; Derya Bachir; Christopher Nelke; et al. (Nature Communications)
Abstract K2P2.1 (gene: Kcnk2), a two-pore-domain potassium channel, regulates leukocyte transmigration across the blood-brain barrier by a yet unknown mechanism. We demonstrate that Kcnk2 −/− mouse brain microvascular endothelial cells (MBMECs) exhibit an altered cytoskeletal structure and surface morphology with increased formation of membrane protrusions. Cell adhesion molecules cluster on those protrusions and facilitate leukocyte adhesion and migration in vitro and in vivo. We observe downregulation of K2P2.1 and activation of actin modulating proteins (cofilin 1, Arp2/3) in inflamed wildtype MBMECs. In the mechanosensitive conformation, K2P2.1 shields the phospholipid PI(4,5)P2 from interaction with other actin regulatory proteins, especially cofilin 1. Consequently, after stimulus-related K2P2.1 downregulation and dislocation from PI(4,5)P2, actin rearrangements are induced. Thus, K2P2.1-mediated regulatory processes are essential for actin dynamics, fast, reversible, and pharmacologically targetable.